PERGANTIAN GUBERNUR SEBAGAI KONFLIK INTERNAL PADA MASA PEMERINTAHAN UTSMAN BIN AFFAN - Hambaliana, Dandie; Nurulloh, Deden Gumilang Masdar (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2022)
This research will discuss the change of governor as a conflict during the reign of Utsman bin Affan radhiallahu anhu. Utsman bin Affan was the third caliph in the Rashidun Khulafaur period to replace Umar bin Khattab who died. This research utilizes literature or literature. The research method used is the historical research method which includes heuristics, verification, interpretation, and historiography by utilizing the Role Theory proposed by Ralf Dahrendorf. The results of the study show that the change of governor by Utsman bin Affan resulted in conflict within the Muslim community. This condition shows how the caliph Utsman bin Affan had to try to reduce the chaos that occurred to his government, even the event was one of the rebellions that caused Utsman bin Affan's death.